Description of Abnormal Breathing Is Associated With Improved Outcomes and Delayed Telephone Cardiopulmonary Resuscitation Instructions. Issue 9 (29th August 2017) - Fukushima, Hidetada; Panczyk, Micah; Hu, Chengcheng; Dameff, Christian; Chikani, Vatsal; Vadeboncoeur, Tyler; Spaite, Daniel W.; Bobrow, Bentley J.
Abstract : Background: Emergency 9‐1‐1 callers use a wide range of terms to describe abnormal breathing in persons with out‐of‐hospital cardiac arrest (OHCA). These breathing descriptors can obstruct the telephone cardiopulmonary resuscitation (CPR) process. Methods and Results: We conducted an observational study of emergency call audio recordings linked to confirmed OHCAs in a statewide Utstein‐style database. Breathing descriptors fell into 1 of 8 groups (eg, gasping, snoring). We divided the study population into groups with and without descriptors for abnormal breathing to investigate the impact of these descriptors on patient outcomes and telephone CPR process. Callers used descriptors in 459 of 2411 cases (19.0%) between October 1, 2010, and December 31, 2014. Survival outcome was better when the caller used a breathing descriptor (19.6% versus 8.8%, P <0.0001), with an odds ratio of 1.63 (95% confidence interval, 1.17–2.25). After exclusions, 379 of 459 cases were eligible for process analysis. When callers described abnormal breathing, the rates of telecommunicator OHCA recognition, CPR instruction, and telephone CPR were lower than when callers did not use a breathing descriptor (79.7% versus 93.0%, P <0.0001; 65.4% versus 72.5%, P =0.0078; and 60.2% versus 66.9%, P =0.0123, respectively). The time interval between call receipt and OHCA recognition was longer when the caller used a breathing descriptor (118.5 versus 73.5 seconds, P <0.0001). Conclusions: Descriptors of abnormal breathing are associated with improved outcomes but also with delays in the identification of OHCA. Familiarizing telecommunicators with these descriptors may improve the telephone CPR process including OHCA recognition for patients with increased probability of survival.